The role of frugivorous birds in the dispersal of shrubs in submontane zone of tropical forest, West Java, Indonesia - RUHYAT PARTASASMITA (Smujo International, 2015)
Abstract. Partasasmita R. 2015. The role of frugivorous birds in the dispersal of shrubs in submontane tropical forest, West Java, Indonesia. Nusantara Bioscience 7: 144-148. Shrubs are widely distributed, from lowland to mountainous area. Submontane forest zone is one of many ecosystem types rich in many species of shrub. The success of plant growth and establishment depends on the role of the seed dispersal agents. This study of shrub seed dispersal by frugivorous birds has been conducted in tea plantation area of Panaruban, Subang, West Java. To get seeds trapped in feces, samples of feces were collected from birds trapped in mist nets and from fecal dropped count method. The study sites were tea plantation which had been neglected for five years and bush in a secondary forest nearby. The results showed that seeds of 7 species of shrub were found in the feces of six species of frugivorous birds trapped in mist nets and one species of bird from fecal dropped count method. Based on feces analysis, of the seven shrub species, Clidemia hirta was dispersed mostly by Dicaeum trigonostigma, and then by Pycnonotus aurigaster. Sambucus javanica was mostly dispersed by Pycnonotus goiavier and Scissirostrum dubium. The germination rate of seeds collected from feces was 1.43-5.71% higher than that of seeds which had not passed through the bird’s digestive tract.